The dynamics of health policies in Mozambique 1975–85 - Walt, Gill; Cliff, Julie (Health Policy and Planning, 1986)
In 1985 Mozambique commemorated its tenth year of independence against a background of a continuing need to defend the country, not only against the actions of the externally-backed Mozambique National Resistance (MNR), but also against drought, acute food shortages and a world economic recession. These external factors have significant implications for the implementation of Mozambique's health policy. The MNR has chosen as deliberate targets for attack: health posts, health centres, rural hospitals, even health workers. Ambushes and the mining of roads and electricity pylons have interrupted the supply and storage of drugs, the maintenance of immunization programmes and the support and supervision of health personnel. Food and water shortages have put lives at risk. These external factors are exacerbating some of the urban and rural class struggles which have become more apparent in the last few years and which, taken together, challenge the direction of health policy. This paper first sets the geographical context of Mozambique's independence. It goes on to explore how health policy was forged through theory and practice over a ten-year period of armed struggle. A brief discussion of health in the colonial state and some of the constraints faced in the first years of independence follows. Finally an attempt is made to assess the effects of both internal struggles and external factors on health policy ten years after independence.
Keywords: *indexed; G - Mozambique / Moçambique; L - english / inglês; health / saúde